Fisheries co-management for Kota Marudu, Sabah - Mohamed Arshad, Fatimah (Universiti Putra Malaysia Press, 2012)
This book is based on a research project title ‘Co-management Arrangement for Kota Marudu, Sabah’ which is funded by the Ministry of Science, Technology and Innovation (MOSTI) through National Oceanography Directorate (NOD) in early 2009. The study was to explore the possibility of introducing fisheries co-management among the locals to manage their coastal resource to ensure sustainability. Kota Marudu, Sabah was chosen as a study area based on apparent over exploitation of the fisheries resource as proven by a significant decline in fish catch and rampant poverty in the fisher community. The area also showed physical degradation due to logging activities in the hinterlands, development in the coastal area (which includes reclamation of swamps and clear-felling of mangroves for agricultural land). Fish bombing and cyanide fishing activities threaten the reefs in the area.